Insulin-Like Growth Factor Binding Protein 2 Is Associated With Biomarkers of Alzheimer’s Disease Pathology and Shows Differential Expression in Transgenic Mice - Bonham, Luke W.; Geier, Ethan G.; Steele, Natasha Z. R.; Holland, Dominic; Miller, Bruce L.; Dale, Anders M.; Desikan, Rahul S.; Yokoyama, Jennifer S.; , Alzheimer’s Disease Neuroimaging Initiative (Frontiers in Neuroscience, 2018)
There is increasing evidence that metabolic dysfunction plays an important role in Alzheimer’s disease (AD). Brain insulin resistance and subsequent impairment of insulin and insulin-like growth factor (IGF) signaling are thought to be linked with the neurodegenerative and clinical features of AD. Nevertheless, how the brain insulin/IGF signaling system is altered in AD and the effects of these changes on AD pathobiology are not well understood. IGF binding protein 2 (IGFBP-2) is an abundant cerebral IGF signaling protein and there is early evidence suggesting it associates with AD biomarkers. We evaluated the relationship between protein levels of IGFBP-2 with cerebrospinal fluid (CSF) biomarkers and neuroimaging markers of AD progression in 300 individuals from across the AD spectrum. CSF IGFBP-2 levels were correlated with CSF tau levels and brain atrophy in non-hippocampal regions. To further explore the role of IGFBP2 in tau pathobiology, we evaluated the expression of IGFBP2 brain tissue from transgenic mouse models of tauopathy (P301L-tau) as well as AD (TASTPM) and determined the cell types that most highly express IGFBP2. IGFBP2 expression in transgenic mouse models of neurodegenerative disease was only significantly different from wild-type mice in cortex, but not in hippocampus. In both humans and mice, IGFBP2 is most highly expressed in astrocytes. Taken together, our findings suggest that IGFBP-2 may be linked to tau pathology and provides further evidence for a relationship between metabolic dysregulation and neurodegeneration. Our results also raise the possibility that this relationship may extend beyond neurons.